Intimate relationships and social change : the dynamic nature of dating, mating, and coupling - Scott, Christina L.; Blair, Sampson Lee (Contemporary perspectives on family research ;, 2017)
This multidisciplinary volume provides a unique and truly global collection of research on the nature of dating, mating, and coupling, as they occur across a variety of cultures in dynamically shifting societies.